Accident d`évolution des dents de sagesse et sport de haut niveau - Denis, F.; Guillerminet, V.; Ahossi, V. (Science & Sports, 2016)
The evolution of wisdom teeth accidents is observed in late adolescence and in young adults between 16 and 25 years. The top athletes are particularly exposed to inflammatory and infectious risks during the development of these teeth. The high-level sports are a singular subject for which the management of this health problem must be discussed. As part of this development, we will present the symptoms associated with the evolution of wisdom teeth accidents on the one hand, and on the other hand, we will discuss the consequences of this health problem and its treatment for a top athlete. Finally, we will discuss guidelines for the avulsion of third molars.